ШАҢАРАҚТА ПЕРЗЕНТ ТӘРБИЯСЫНДАҒЫ МАШҚАЛАЛАРДЫ ШЕШИЎДЕ МИЛЛИЙ ҲӘМ УЛЫЎМАИНСАНЫЙЛЫҚ ҚӘДИРИЯТЛАРДАН ПАЙДАЛАНЫЎ - Сапарбаева, Т.Т. (SCIENCE and SOCIETY, 2017)
The article contains valuable advice and recommendations on the problems of children’s education in the family. There have been studied the basic concepts in using national and general human values in the education of children.